Japanese fashion cultures dress and gender in contemporary Japan - Monden, Masafumi (London Bloomsbury, 2015)
"From rococo to Edwardian fashions, Japanese street style has reinvented many western dress styles, reinterpreting and altering their meanings and messages in a different cultural and historical context. This wide ranging and original study reveals the complex exchange of styles and what they represent in Japan and beyond, contesting common perceptions of gender in Japanese dress and the notion that non-western fashions simply imitate western styles. Through case studies focussing on fashion image consumption in style tribes such as Kamikaze Girls, Lolita, Edwardian, Ivy Style, Victorian, Romantic and Kawaii, this ground-breaking book investigates the complexities of dress and gender and demonstrates the flexible nature of contemporary fashion and style exchange in a global context. Japanese Fashion Cultures will appeal to students and scholars of fashion, cultural studies, gender studies, media studies and related fields."-- Provided by publisher.
Machine generated contents note: -- 1. Introducing Japanese Fashion, Past and Present2. Lost in a Gaze: Young Men and Fashion in Contemporary Japan3. Boy's Elegance: A Liminality of Boyish Charm and Old-World Suavity4. Glace; Wonderland: Cuteness, Sexuality and Young Women5. Ribbons and Lace: Girls, Decorative Femininity and Androgyny6. An Ivy Boy and a Preppy Girl: Style Import-Export7. Concluding Japanese Fashion Cultures, Change and Continuity Bibliography Index.
Includes bibliographical references and index.
Keywords: Fashion -- Japan -- History; Clothing and dress -- Japan -- History; Clothing and dress -- Social aspects -- Japan